Improving Students’ Reading Comprehension of Descriptive Text Through Multiple Intelligences Strategy at SMP Swasta Harvard Medan - Septa Riana Sidauruk; Enni Maisaroh (Edumaspul: Jurnal Pendidikan, 2025)
The Multiple Intelligences Strategy will be used in this project to help seventh-grade students at SMP Swasta Harvard Medan enhance their reading comprehension. A Classroom Action Research (CAR) design was used in the study, and it was conducted in two cycles with four steps each: planning, action, observation, and reflection. The study's subjects comprised a number of students who had trouble comprehending descriptive writings, especially when it came to recognizing the key concepts and supporting elements.Observation sheets, interviews, field notes, documentation, and reading comprehension assessments were used to gather data. The results of classroom observations and the evaluation of students' performance through pre-test and post-test evaluations were the main focus of the qualitative and quantitative methodologies used to examine the data. The results showed that after using the Multiple Intelligences Strategy, students' reading comprehension significantly improved. The findings showed that by leveraging the different forms of intelligence that each learner possesses, this approach successfully assisted students in understanding descriptive texts. In order to improve students' interest, understanding, and learning outcomes, the study suggests using this method more widely in reading education.